Revisiting Activity of Some Nocodazole Analogues as a Potential Anticancer Drugs Using Molecular Docking and DFT Calculations - Khattab, Muhammad; Al‐Karmalawy, Ahmed A. (Frontiers in Chemistry, 2021)
Although potential anticancer activities of benzimidazole-based anthelmintic drugs have been approved by preclinical and clinical studies, modes of binding interactions have not been reported so far. Therefore in this study, we aimed to propose binding interactions of some benzimidazole-based anthelmintics with one of the most important cancer targets (Tubulin protein). Studied drugs were selected based on their structural similarity with the cocrystallized ligand (Nocodazole) with tubulin protein. Quantum mechanics calculations were also employed for characterization of electronic configuration of studied drugs at the atomic and molecular level. Order of binding affinities of tested benzimidazole drugs toward colchicine binding site on tubulin protein is as follows: Flubendazole ˃ Oxfendazole ˃ Nocodazole ˃ Mebendazole ˃ Albendazole ˃ Oxibendazole ˃ Fenbendazole ˃ Ciclobendazole ˃ Thiabendazole ˃ Bendazole. By analysing binding mode and hydrogen bond length between the nine studied benzimidazole drugs and colchicine binding site, Flubendazole was found to bind more efficiently with tubulin protein than other benzimidazole derivatives. The quantum mechanics studies showed that the electron density of HOMO of Flubendazole and Mebendazole together with their MEP map are quite similar to that of Nocodazole which is also consistent with the calculated binding affinities. Our study has ramifications for considering the repurposing of Flubendazole as a promising anticancer candidate.